2017
DOI: 10.1111/1742-6723.12818
|View full text |Cite
|
Sign up to set email alerts
|

Medical scribes have no impact on the patient experience of an emergency department

Abstract: We found no evidence that scribes reduce patient satisfaction during emergency consultations, nor prompt discomfort that might cause a patient to withhold information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
(55 reference statements)
1
24
0
Order By: Relevance
“…9 Since publication of those reviews, there have been several additional studies related to the effect of scribes on patient satisfaction. Although patients have reported positive attitudes toward scribes and perceived improvement of provider-patient interactions, [10][11][12] no studies have found a quantitative difference in patient's satisfaction with providers. 11,[13][14][15][16][17] Conclusions are further limited by heterogeneity in the methodology for assessing patient satisfaction in all of these studies, including many studies that created their own surveys and metrics.…”
Section: Discussionmentioning
confidence: 99%
“…9 Since publication of those reviews, there have been several additional studies related to the effect of scribes on patient satisfaction. Although patients have reported positive attitudes toward scribes and perceived improvement of provider-patient interactions, [10][11][12] no studies have found a quantitative difference in patient's satisfaction with providers. 11,[13][14][15][16][17] Conclusions are further limited by heterogeneity in the methodology for assessing patient satisfaction in all of these studies, including many studies that created their own surveys and metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The NPS has been used in EM in the evaluation of patient experience, as well as staff satisfaction with particular interventions; however, as far as we know, not in the assessment of staff wellbeing. We were unable to find any assessment of reliability and validity of the NPS in EM literature.…”
Section: Discussionmentioning
confidence: 99%
“…The network (six campuses and one ED) has 832 beds. The tertiary ED cares for mainly English‐speaking, older patients, who are likely to have comprehensive private health insurance and high health literacy . There are 24 000 ED attendances annually (admission rate 50%).…”
Section: Methodsmentioning
confidence: 99%
“…The tertiary ED cares for mainly English-speaking, older patients, who are likely to have comprehensive private health insurance and high health literacy. 20 There are 24 000 ED attendances annually (admission rate 50%). Consultants, experienced continuing medical officers or senior advanced trainee doctors provide direct patient care.…”
Section: Settingmentioning
confidence: 99%